Landscapes : - Winchester, Hilary P. M. (Pearson / Prentice Hall, 2003)
Landscapes is a timely and well-written analysis of the meaning of cultural landscapes. The book delves into the layers of meaning that are invested in ordinary landscapes as well as landscapes of spectacle and power. Landscapes is a powerful and vivid application of the new cultural geography to case studies not previously visited within cultural geography texts.